Pengaturan Jual Beli Sex Toys di Marketplace Perspektif Sadd Adz-Dzariah - Mayang Sekar Ningrum Nasution; Cahaya Permata (Dinasti Review Publisher, 2024)
Sex toys on the Shopee marketplace are traded freely. Even though sex toys are not products that should be accessible to all audiences. So the aim of this research is to find out how the practice of buying and selling sex toys in the marketplace is, to find out the regulations for buying and selling in the marketplace, and to find out how the buying and selling of sex toys in the marketplace is regulated from a sadd ad?-d?ar?'ah perspective. This type of research is normative juridical with a conceptual approach and a statute approach. Data was collected through document study and analyzed descriptively. The results of this research show that the marketing and offering of sex toys on the Shopee marketplace is very free. There is no age limit and no special qualifications that regulate it. This has a negative impact on children, because it provides an avenue for promiscuity. Apart from that, sex toys are also a means for someone to carry out intimate acts which are prohibited by Islam. So, to prevent this act, there should be regulations that prohibit the free distribution of sex toys.